Indigenous Cellulosic Raw Materials for the Production of Pulp, Paper and Board - Bhat, R. V.; Kaushik, H. K. (Indian Forester, 1955)
Laboratory experiments on the production of sulphate and soda pulps for wrapping papers from Acacia decurrens Willd. (wattle wood) are described. The results of pilot plant experiments are also included. This investigation has shown that A. decurrens is a promising raw material for the production of wrapping papers in high yields and of satisfactory strength properties. Since this wood is short-fibred, the average fibre length being 0.86 mm., it will be necessary to mix a suitable quantity of a long-fibred pulp such as bamboo sulphate pulp with the wattle wood pulp for manufacturing wrapping papers on commercial paper machines. Five samples of wrapping papers made on the pilot plant of this Institute are appended in this bulletin.